Reliable battery-aware cooperative multicasting for MBS WiMAX traffic - Elrabiei, Sara Moftah; Habaebi, Mohamed Hadi (Scientific Research, 2011)
Recently, relay agents selection schemes were introduced to support downlink multicasting in WiMAX sin-gle frequency networks. Such schemes were devised to work cooperatively in order to facilitate reliable Mul-ticast Broadcast Multimedia Services (MBMS) traffic delivery over wireless channels without any consid-eration to mobile relay agents’ battery energy levels. In this paper, we introduce a battery-aware balancing algorithm to operate in conjunction with these relay agents selection schemes proposed in the open literature. A simulation model, used to present the effect of “before” and “after” the battery–awareness selection crite-rion, highlighted the benefit of using such algorithms in prolonging network lifetime with emphasis on reli-able delivery.